If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.13 + -1(x + 1) = -0.03(4 + -1x) Reorder the terms: 0.13 + -1(1 + x) = -0.03(4 + -1x) 0.13 + (1 * -1 + x * -1) = -0.03(4 + -1x) 0.13 + (-1 + -1x) = -0.03(4 + -1x) Combine like terms: 0.13 + -1 = -0.87 -0.87 + -1x = -0.03(4 + -1x) -0.87 + -1x = (4 * -0.03 + -1x * -0.03) -0.87 + -1x = (-0.12 + 0.03x) Solving -0.87 + -1x = -0.12 + 0.03x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03x' to each side of the equation. -0.87 + -1x + -0.03x = -0.12 + 0.03x + -0.03x Combine like terms: -1x + -0.03x = -1.03x -0.87 + -1.03x = -0.12 + 0.03x + -0.03x Combine like terms: 0.03x + -0.03x = 0.00 -0.87 + -1.03x = -0.12 + 0.00 -0.87 + -1.03x = -0.12 Add '0.87' to each side of the equation. -0.87 + 0.87 + -1.03x = -0.12 + 0.87 Combine like terms: -0.87 + 0.87 = 0.00 0.00 + -1.03x = -0.12 + 0.87 -1.03x = -0.12 + 0.87 Combine like terms: -0.12 + 0.87 = 0.75 -1.03x = 0.75 Divide each side by '-1.03'. x = -0.7281553398 Simplifying x = -0.7281553398
| 2(6-6x)+7(x-7)=Ax+B | | 14/3+1/5t=7 | | 3(5x+6)=-12+15 | | 0=x^2-14x+24 | | 6u^3(-2u^5)= | | 0=8h^2+12h-4896 | | y=2x^2-x+2 | | 3x(x-9)=13x^2-28x | | 1=15t-5t^2 | | 3.6q-1.2-4.1q=-1.5q-5.1 | | (x^2+12x)+(3x^2+20)=180 | | 6w=3P-6l | | 9xsquared+4=12x | | 0=x^2-12x+11 | | 8(t-4)+4t=4(3t+3)-9 | | 7h+2h-5=19 | | 8x-4=5x+1 | | y=k(x-a)(x-b) | | 3+4x=2(2x+2) | | 4x^2+12X=160 | | -5y+6=-8y+12 | | 1.001/7=b | | x+x+17+2(x-30)=695 | | 11x+36=6x+6 | | 4/3*(3.14)*10^3 | | x+10x+25(33-2x)=182 | | 9xy-2y=-5 | | 11x-7+2x-3=10x-3+2x | | 2x-5+(3x+4)=5x-1 | | -16+-3x-16= | | -8x+4x-24=-28 | | 3-t/23+5=12 |